2005
DOI: 10.1086/430872
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Luminosity Function of the Globular Cluster M10

Abstract: We present the I-band luminosity function of the differentially reddened globular cluster M10. We combine photometric analysis derived from wide-field (23' x 23') images that include the outer regions of the cluster and high-resolution images of the cluster core. After making corrections for incompleteness and field star contamination, we find that the relative numbers of stars on the lower giant branch and near the main-sequence turnoff are in good agreement with theoretical predictions. However, we detect si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Observations were obtained with GNIRS on Gemini North as apart of GN-2017A-Q-70. We used the short camera, the 0.3" slit, and the 110.5 lines mm −1 a ID From Pollard et al (2005) b Ks magnitudes from 2MASS (Skrutskie et al 2006) c AGB Star grating to achieve a resolution of R ≈ 3500 in the K band. We observed the wavelength range between 22800Å-24000Å to measure 13 C 16 O features at 2.34 µm and 2.37 µm.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations were obtained with GNIRS on Gemini North as apart of GN-2017A-Q-70. We used the short camera, the 0.3" slit, and the 110.5 lines mm −1 a ID From Pollard et al (2005) b Ks magnitudes from 2MASS (Skrutskie et al 2006) c AGB Star grating to achieve a resolution of R ≈ 3500 in the K band. We observed the wavelength range between 22800Å-24000Å to measure 13 C 16 O features at 2.34 µm and 2.37 µm.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Finally, our conclusions are summarized in Section 7. Pollard et al (2005). Our sample includes RGB stars plotted as red stars and AGB stars as red circles.…”
Section: Introductionmentioning
confidence: 99%
“…NGC 6254 has previously been studied using ground-based facilities by Rosenberg et al (2000b) andvon Braun et al (2002) in VI and by Pollard et al (2005) in BVI. bands.…”
Section: Ngc 6254-m 10 (Figure 11)mentioning
confidence: 99%
“…Currently developed and available theoretical models of red giant evolution seem not to predict any obvious peculiarity of the evolution of stars in the lower RGB, appropriate to the red giants with the characteristics typical for GC stars. This general conclusion can be checked, for example, by examining various sets of theoretical LFs developed by different groups and applied, in particular, by Hargis et al (2004), Pollard et al (2005), Fekadu et al (2007) for the comparison of the theoretical LFs with observed RGB LFs of a number of GCs.…”
Section: The Empirical Results Versus Theorymentioning
confidence: 99%
“…NGC 6254 (M10). In the I-band RGB LF by Pollard et al (2005), there is an obvious dip at I ≈ 15.0, and the RGB base is at I ≈ 16.3. Therefore, the magnitude difference ΔI dip base is around 1.3 mag.…”
Section: Additional Evidence Of the Knee-related Dip/gap In The Lowermentioning
confidence: 95%